Takaful: products and instruments, communication and management in Takaful industry - Hassan, Rusni; Harun, Hafiza; Salman, Syed Ahmed (Malaha PLT, 2023)
The rapid growth of Islamic finance at the global level lead the industry to form a robust governance system to ensure its overall survival. Conventional or Islamic institutions require solid corporate governance to ensure effective and efficient control and operation. However, this realization of the importance of corporate governance was not always so obvious. Financial crises that had shaken the foundations of the financial system are arguably critical contributors to the growing awareness of corporate governance. Islamic financial institutions (IFIs) are followers in that regard.